Widely Distributed and Predominant CTX-M Extended-Spectrum β-Lactamases in Amsterdam, The Netherlands - al Naiemi, N. (American Society for Microbiology, 2006)
Three hundred sixty Enterobacteriaceae and nonfermenting gram-negative bacilli, isolated during one week in May 2004 at five hospitals in Amsterdam, The Netherlands, were evaluated for the presence of extended-spectrum beta-lactamases (ESBLs). A prevalence of 7.8% was found, in contrast to the 1% observed in 1997. CTX-M ESBLs dominated, and four types were identified in 18 isolates.